A Thirty four years old university extension program: “Every Crasy With His Mania” - Guimarães Firme Lorenzon, Anallu; Alves Prates, Tânia Mara; Eckhardt, Eneida von (Guará Journal, 2017)
This Program from the Federal University of Espírito Santo (UFES) develops therapeutic actions for children, adolescents and adults derived from UFES and from the Children’s Hospital. People suffer from their psychic structure and from the challenges of everyday life. We hear and treat them to make possible that they change anxieties, conflicts, disorders, destructive actions for better solutions, facing the pain of living. The treatments are realized by professional and students under counseling. This clinic includes first the reception of the patient and his family. After we try to understand their life history and make psychic examination in order to construct an individual therapeutic project that may include individual sessions, psychopharmacology, group or familiar treatment and therapeutic workshops (Imagination, Tales, Modeling, Expression, Music and Painting). The patient is monitored by interdisciplinary teams. They become responsible for their treatment. In the last two years we realized 1679 attendances. These resources are revealing symbolic substitutions that favor the treatment. The conflicts and familiar mismatches have diminished and this has been favorable for the treatment